Creative Pathways Through High School: A Response to John Dorrer, “Do We Have the Workforce Skills for Maine’s Innovation Economy?” - Most, Sylvia (Maine Policy Review, 2014)
In this commentary on a recent Maine Policy Review article by John Dorrer, the author asks whether Maine is on the right track in its current emphasis on “college for all.” Her commentary suggests that students and employers might be better served by revisiting an earlier model of providing more vocational education opportunities.
Keywords: Maine; education policy; post-secondary education; vocational education